2006
DOI: 10.1103/physrevlett.97.237203
|View full text |Cite
|
Sign up to set email alerts
|

Induced Random Fields in theLiHoxY1xF4Quantum Ising Magnet in a Transverse Magnetic Field

Abstract: The LiHoxY1-xF4 magnetic material in a transverse magnetic field Bx x perpendicular to the Ising spin direction has long been used to study tunable quantum phase transitions in a random disordered system. We show that the Bx-induced magnetization along the x direction, combined with the local random dilution-induced destruction of crystalline symmetries, generates, via the predominant dipolar interactions between Ho3+ ions, random fields along the Ising z direction. This identifies LiHoxY1-xF4 in Bx as a new r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 23 publications
6
127
0
Order By: Relevance
“…We have also ignored off-diagonal terms in the dipolar Hamiltonian, which result in an effective random transverse field. 16,17,25 Including these terms in the calculation would be an important next step in interpreting the measurements on LiHo x Y 1−x F 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also ignored off-diagonal terms in the dipolar Hamiltonian, which result in an effective random transverse field. 16,17,25 Including these terms in the calculation would be an important next step in interpreting the measurements on LiHo x Y 1−x F 4 .…”
Section: Discussionmentioning
confidence: 99%
“…14,15,16,17 Yet a non-perturabative calculation beyond mean-field of several fundamental properties such as the specific heat and linear susceptibility is lacking even for the first-order model described by Eq. (1).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the experimental procedure for creating such a random field Ising system is convoluted and typically considers a diluted Ising antiferromagnet in a uniform longitudinal field B z [66,67]. Analytical [33,62,63,64,65] and numerical [62,63,64] studies have shown, rather convincingly, that the presence of B x -induced random fields h z i can explain the two aforementioned puzzles observed in LiHo x Y 1−x F 4 in nonzero B x , in both the diluted FM regime and in the SG regime. In particular, the B x -induced random fields h z i eliminate the divergence of the nonlinear susceptibility χ 3 in the spin glass regime x 0.25 [32,62,64].…”
Section: Transverse Field and Random Field Effects In Lihomentioning
confidence: 99%
“…(2) when the occupation factor i = 1 [62,63], the transverse field B x induces not only quantum fluctuations, but also random fields [43,44,47], h z i , that couple linearly to theẑ component of σ i [32,33,62,63,64,65]. There are two key physical ingredients responsible for these random fields.…”
Section: Transverse Field and Random Field Effects In Lihomentioning
confidence: 99%
“…In particular, it should not be a cause of the spin-glass freezing. Another effect omitted in our simulation is the generation of random magnetic fields due to the dilution, which breaks the crystalline symmetry [20,21,22]. However, the effect of this term should be to increase fluctuations and lower the critical temperature for both the ferromagnetic and the spin-glass phase.…”
mentioning
confidence: 99%